Development of Rifapentine-Loaded PLGA-Based Nanoparticles: In vitro Characterisation and in vivo Study in Mice - Liang Q (Dove Medical Press, 2020)
Qiuzhen Liang1 ,* Haibin Xiang1 ,* Xinyu Li,2 Chunxia Luo,2 Xuehong Ma,2 Wenhui Zhao,2 Jiangtao Chen,1 Zheng Tian,1 Xinxia Li,2 Xinghua Song3,4 1Department of Orthopaedics, The First Affiliated Hospital of Xinjiang Medical University, Urumqi 830054, People’s Republic of China; 2School of Pharmacy, Xinjiang Medical University, Urumqi 830011, People’s Republic of China; 3Department of Orthopaedic, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong Province 510630, People’s Republic of China; 4Department of Orthopaedic, The Affiliated Shunde Hospital of Jinan University, Foshan, Guangdong Province 528303, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinghua SongDepartment of Orthopaedic, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong Province 510630, People’s Republic of ChinaEmail 811789561@qq.comXinxia LiSchool of Pharmacy, Xinjiang Medical University, No. 393, Xinyi Road, Urumqi 830011, People’s Republic of ChinaEmail lixxphar@163.comBackground: Tuberculosis (TB) is a leading cause of death amongst infectious diseases. The poor response to antitubercular agents necessitates the long-term use of high drug doses, resulting in low patient compliance, which is the main reason for chemotherapy failure and contributes to the development of multidrug-resistant TB. Patient non-compliance has been a major obstacle in the successful management of TB. The aim of this work was to develop and characterise rifapentine (RPT)-loaded PLGA-based nanoparticles (NPs) for reducing dosing frequency.Methods: RPT-loaded PLGA and PLGA–PEG NPs were prepared using premix membrane homogenisation combined with solvent evaporation method. The resulting NPs were characterised in terms of physicochemical characteristics, toxicity, cellular uptake and antitubercular activity. NPs were further evaluated for pharmacokinetic and biodistribution studies in mice.Results: The resulting NPs showed suitable and safe physicochemical characteristics and could be taken up by macrophages. RPT-loaded NPs were more effective against Mycobacterium tuberculosis than free RPT. In vivo studies revealed that NPs could improve pharmacokinetic parameters, particularly for RPT/PLGA–PEG NPs. Moreover, both formulations had no toxicity to the organs of mice and could reduce hepatotoxicity.Conclusion: The application of PLGA-based NPs as sustained-release delivery vehicles for RPT could prolong drug release, modify pharmacokinetics, increase antitubercular activity and diminish toxicity, thereby allowing low dosage and frequency.Keywords: tuberculosis, rifapentine, drug delivery system, nanoparticles